Authentication of Punica granatum L.: Development of SCAR markers for the detection of 10 fruits potentially used in economically motivated adulteration. (1st July 2016) - Marieschi, Matteo; Torelli, Anna; Beghé, Deborah; Bruni, Renato
Highlights: A SCAR-based method was set up to detect ten bulking agents in pomegranate products. Specific markers allowed the rapid identification of all adulterants. Each adulterant can be detected in amounts as low as 1%. The method was successfully applied to different commercial samples. Abstract: The large commercial success of pomegranate increase the likelihood of economically motivated adulteration (EMA), which has been gradually spotted with the undeclared addition of anthocyanin-rich plants or cheaper fruit juices used as bulking and diluting agents. A method based on Sequence-Characterized Amplified Regions (SCARs) was developed to detect the presence of Aristotelia chilensis, Aronia melanocarpa, Dioscorea alata, Euterpe oleracea, Malus × domestica, Morus nigra, Sambucus nigra, Vaccinium macrocarpon, Vaccinium myrtillus, Vitis vinifera as bulking agents in Punica granatum . The method enabled the unequivocal detection of up to 1% of each adulterant, allowing the preemptive rejection of suspect samples. The recourse to such method may reduce the number of samples to be subjected to further phytochemical analyses when multiple batches have to be evaluated in a short time. Vice versa, it allows the cross-check of suspect batches previously tested only for their anthocyanin profile. The dimension of the amplicons is suitable for the analysis of degraded DNA obtained from stored and processed commercial material. Proper SCAR markers may represent a fast, sensitive, reliable and low-cost screening method for the authentication of processed commercial pomegranate material.